Solar cell front anti-reflection film and solar cell
By stacking titanium dioxide films and tin dioxide films on a solar cell silicon substrate, combining silicon nitride and silicon oxide films to adjust the film layer thickness and refractive index, the problem of low light absorption and conversion efficiency in the prior art is solved. Achieve higher light utilization and battery performance improvements.
Patent Information
- Application Number
- CN202420189113.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-25
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2034-01-25
AI Technical Summary
The front anti-reflection film structure design of existing solar cells is relatively single, and the space for optimization and improvement is limited, resulting in low light absorption and conversion efficiency.
Using a titanium dioxide film and a tin dioxide film sequentially laminated on a silicon substrate, and adding a silicon nitride film and silicon oxide film thereon, a specific combination is formed to improve the light utilization rate and Passivation effect.
By optimizing the film layer structure, the light absorption coefficient and conversion efficiency of solar cells are improved, the reflectance is reduced, and the light utilization rate and cell performance are improved.
Smart Images

Figure CN222190739U_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to the technical field of solar cells, in particular to a solar cell front anti-reflection film and a solar cell. Background Art
[0002] In order to maximize the use of solar energy, increase the light absorption of the battery, and improve the conversion efficiency of the battery, the current method is to deposit an anti-reflection film layer on the front of the battery. Its common structure is a multilayer structure composed of silicon nitride and silicon oxide. Through the gradient refractive index of the film layer, combined with the chemical passivation and body passivation effects of the material, the defects of the battery can be passivated to a certain extent and carrier recombination can be reduced. However, the multilayer film structure composed of silicon nitride and silicon oxide has a relatively simple film layer design, limited room for optimization and improvement, poor anti-reflection effect, and limited passivation effect, resulting in lower light absorption and conversion efficiency. Utility Model Content
[0003] The technical problem to be solved by the utility model is to provide a solar cell front anti-reflection film, which can improve the light utilization efficiency and the conversion efficiency of the solar cell.
[0004] The technical problem that the utility model needs to solve is to provide a solar cell with high conversion efficiency.
[0005] In order to solve the above technical problems, the utility model provides a solar cell front anti-reflection film, which is arranged on a silicon substrate and includes a titanium dioxide film and a tin dioxide film stacked in sequence;
[0006] The refractive index of the tin dioxide film is smaller than that of the titanium dioxide film, and the thickness of the tin dioxide film is the same as or different from that of the titanium dioxide film.
[0007] As an improvement of the above technical solution, the thickness of the titanium dioxide film is 5nm to 15nm, and the refractive index is 2.1 to 2.3;
[0008] The tin dioxide film has a thickness of 5nm to 15nm and a refractive index of 1.9 to 2.0.
[0009] As an improvement of the above technical solution, it also includes a silicon nitride film disposed on the tin dioxide film;
[0010] The refractive index of the silicon nitride film is smaller than the refractive index of the tin dioxide film.
[0011] As an improvement of the above technical solution, the thickness of the silicon nitride film is 10nm to 150nm, and the refractive index is 1.5 to 1.8.
[0012] As an improvement of the above technical solution, it also includes a silicon oxide film arranged on the tin oxide film, and the refractive index of the silicon oxide film is smaller than the refractive index of the tin oxide film.
[0013] As an improvement of the above technical solution, it also includes a silicon oxide film arranged on the silicon nitride film, and the refractive index of the silicon oxide film is smaller than the refractive index of the silicon nitride film.
[0014] As an improvement of the above technical solution, the thickness of the silicon oxide film is 5nm to 20nm, and the refractive index is 1.1 to 1.4.
[0015] As an improvement of the above technical solution, the silicon nitride film includes a first silicon nitride film, a second silicon nitride film and a third silicon nitride film stacked in sequence;
[0016] The refractive index of the third silicon nitride film is lower than that of the second silicon nitride film, and the refractive index of the second silicon nitride film is lower than that of the first silicon nitride film.
[0017] As an improvement of the above technical solution, the thickness of the first silicon nitride film is 10nm to 20nm, and the refractive index is 1.5 to 1.8;
[0018] The thickness of the second silicon nitride film is 20nm to 50nm, and the refractive index is 1.5 to 1.7.
[0019] The third silicon nitride film has a thickness of 10 nm to 40 nm and a refractive index of 1.5 to 1.7.
[0020] Correspondingly, the present invention also discloses a solar cell, which comprises the above-mentioned solar cell front anti-reflection film.
[0021] Correspondingly, the utility model also discloses a solar cell, which comprises the above-mentioned solar cell front anti-reflection film.
[0022] The implementation of this utility model has the following beneficial effects:
[0023] The utility model discloses an anti-reflection film on the front side of a solar cell, comprising a titanium dioxide film and a tin dioxide film which are sequentially arranged on a silicon substrate, and the refractive index of the titanium dioxide film is greater than that of the tin dioxide film. Through a specific combination of the anti-reflection film materials with similar refractive indices, the problem of optical mismatch and light loss caused by a large refractive index difference between the existing anti-reflection film layers is solved, so that the light absorption coefficient of the front side of the battery is increased, the reflectivity is lowered, the light utilization rate is increased, and the passivation effect is improved, thereby achieving an improvement in the battery conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of the structure of the anti-reflection film on the front side of a solar cell in one embodiment of the utility model;
[0025] Figure 2 It is a schematic structural diagram of a front anti-reflection film for a solar cell in another embodiment of the utility model;
[0026] Figure 3 This is a schematic structural diagram of a solar cell front anti-reflection film in another embodiment of the utility model;
[0027] Figure 4 This is a schematic structural diagram of a front anti-reflection film for a solar cell in another embodiment of the present invention;
[0028] Figure 5 It is a schematic structural diagram of a front anti-reflection film for a solar cell in yet another embodiment of the present invention. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the utility model clearer, the utility model will be further described in detail with reference to the accompanying drawings. It is hereby stated that the directional words such as up, down, left, right, front, back, inside, outside, etc. that appear or will appear in the text of the utility model are only based on the accompanying drawings of the utility model, and are not specific limitations of the utility model.
[0030] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:
[0031] In the present utility model, “preferred” is only used to describe an implementation method or example with better effects, and it should be understood that it does not constitute a limitation on the protection scope of the present utility model.
[0032] In the present utility model, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0033] In the present invention, reference to a numerical range includes both endpoints of the numerical range unless otherwise specified.
[0034] See also Figure 1 The utility model provides a solar cell front anti-reflection film, which is arranged on the front of a silicon substrate 1, and specifically comprises a titanium dioxide film 2 and a tin dioxide film 3 stacked in sequence. Among them, the refractive index of the tin dioxide film 3 is lower than the refractive index of the titanium dioxide film 2, so as to reduce the reflectivity of the incident light and improve the light utilization rate; and this laminated structure can also passivate the dangling bonds on the surface of the silicon substrate 1 well, and the combination of the two improves the conversion efficiency of the solar cell.
[0035] The thickness of the titanium dioxide film 2 is 5 nm to 20 nm, exemplarily 5 nm, 7 nm, 9 nm, 11 nm, 13 nm, 15 nm, 17 nm or 19 nm, but not limited thereto, preferably 5 nm to 15 nm, more preferably 6 nm to 12 nm.
[0036] The refractive index of the titanium dioxide film 2 is 2.1 to 2.35, and is exemplarily 2.13, 2.16, 2.19, 2.22, 2.25, 2.28, 2.31 or 2.34, but is not limited thereto. Preferably, the refractive index of the titanium dioxide film 2 is 2.1 to 2.3, and more preferably 2.2 to 2.3.
[0037] The thickness of the tin dioxide film 3 is 3 nm to 20 nm, and is exemplarily 5 nm, 7 nm, 9 nm, 11 nm, 13 nm, 15 nm, 17 nm or 19 nm, but is not limited thereto. Preferably, the thickness of the tin dioxide film 3 is 5 nm to 15 nm, and more preferably 8 nm to 15 nm.
[0038] The refractive index of the tin dioxide film 3 is 1.9 to 2.0, and is exemplarily 1.91, 1.92, 1.93, 1.94, 1.95, 1.96, 1.97 or 1.98, but is not limited thereto.
[0039] Preferably, in some embodiments, the ratio of the thickness of the titanium dioxide film 2 to the thickness of the tin dioxide film 3 is controlled to be 1:0.8 to 1:1.5. Based on this thickness ratio, the conversion efficiency of the solar cell can be better improved. Exemplarily, the ratio of the thickness of the titanium dioxide film 2 to the tin dioxide film 3 is 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3 or 1:1.4, but is not limited thereto.
[0040] The anti-reflection film on the front side of the solar cell in the utility model is not limited to the above-mentioned titanium dioxide film 2 and tin dioxide film 3, and also includes some anti-reflection films commonly used in the art, such as silicon nitride film, silicon oxynitride film, silicon oxide film, silicon carbide film, etc., but not limited to this. It should be emphasized that when these commonly used anti-reflection films are applied to the structure in the utility model, their refractive index should be less than the refractive index of the tin dioxide film 3 in the utility model.
[0041] Specifically, refer to Figure 2In some embodiments, the front anti-reflection film of the solar cell further includes a silicon nitride film 4 disposed on the tin dioxide film 3, and the refractive index of the silicon nitride film 4 is 1.5 to 1.9, and is exemplarily 1.54, 1.58, 1.62, 1.66, 1.7, 1.74, 1.78, 1.82 or 1.86, but is not limited thereto. Preferably, it is 1.5 to 1.8. The thickness of the silicon nitride film 4 is 10 nm to 150 nm, and is exemplarily 15 nm, 30 nm, 45 nm, 60 nm, 75 nm, 90 nm, 105 nm, 130 nm or 145 nm, but is not limited thereto. Preferably, the thickness of the silicon nitride film 4 is 20 nm to 100 nm, and more preferably 20 nm to 80 nm.
[0042] Specifically, refer to Figure 3 In some embodiments, the solar front anti-reflection film further includes a silicon oxide film 5 disposed on the tin dioxide film 3, and the refractive index of the silicon oxide film 5 is 1.1 to 1.4, and is exemplarily 1.13, 1.16, 1.19, 1.22, 1.25, 1.28, 1.31, 1.34 or 1.37, but not limited thereto. The thickness of the silicon oxide film 5 is 5 nm to 20 nm, and is exemplarily 6 nm, 8 nm, 10 nm, 12 nm, 14 nm, 16 nm or 18 nm, but not limited thereto. Preferably, the thickness of the silicon oxide film 5 is 8 nm to 18 nm, and more preferably 10 nm to 15 nm.
[0043] Preferably, in some embodiments, the solar front anti-reflection film further comprises a silicon nitride film 4 and a silicon oxide film 5 sequentially disposed on the tin dioxide film 3 , and the refractive index of the silicon nitride film 4 is greater than the refractive index of the silicon oxide film 5 .
[0044] Preferably, reference Figure 4 In some embodiments, the solar cell front anti-reflection film further includes a multilayer silicon nitride film 4 disposed on the tin dioxide film 3, and the number of layers may be 2 to 5, but is not limited thereto. The refractive index of the multilayer silicon nitride film 4 decreases from the side close to the tin dioxide film 3 to the side away from the tin dioxide film 3; and the refractive index of each layer of the silicon nitride film 4 is less than the refractive index of the tin dioxide film 3.
[0045] More preferably, in one embodiment, the silicon nitride film 4 includes a first silicon nitride film 41, a second silicon nitride film 42, and a third silicon nitride film 43, which are sequentially arranged on the tin dioxide film 3; and the refractive index of the third silicon nitride film 43 is less than the refractive index of the second silicon nitride film 42, the refractive index of the second silicon nitride film 42 is less than the refractive index of the first silicon nitride film 41, and the thickness of the first silicon nitride film 41 and the thickness of the third silicon nitride film 43 are both less than the thickness of the second silicon nitride film 42.
[0046] Specifically, the thickness of the first silicon nitride film 41 is 8 nm to 25 nm, and is exemplarily 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, 21 nm, 22 nm, 23 nm or 24 nm, but is not limited thereto. Preferably, it is 10 nm to 20 nm, and more preferably, it is 12 nm to 18 nm. The refractive index of the first silicon nitride film 41 is 1.5 to 1.8, and is exemplarily 1.55, 1.6, 1.64, 1.68, 1.72, 1.76 or 1.78, but is not limited thereto. Preferably, it is 1.7 to 1.8.
[0047] The thickness of the second silicon nitride film 42 is 15 nm to 60 nm, and is exemplarily 19 nm, 23 nm, 27 nm, 31 nm, 35 nm, 39 nm, 43 nm, 47 nm, 51 nm, 55 nm or 59 nm, but is not limited thereto. It is preferably 20 nm to 50 nm. It is more preferably 20 nm to 30 nm. The refractive index of the second silicon nitride film 42 is 1.5 to 1.7, and is exemplarily 1.54, 1.6, 1.62, 1.64, 1.66 or 1.68, but is not limited thereto. It is preferably 1.6 to 1.7.
[0048] The thickness of the third silicon nitride film 43 is 5 nm to 45 nm, and is exemplarily 8 nm, 11 nm, 14 nm, 17 nm, 20 nm, 23 nm, 26 nm, 29 nm, 32 nm, 35 nm, 38 nm, 41 nm or 44 nm, but is not limited thereto. It is preferably 10 nm to 40 nm, and more preferably 15 nm to 30 nm. The refractive index of the third silicon nitride film 43 is 1.5 to 1.7, and is exemplarily 1.52, 1.54, 1.56, 1.58, 1.61, 1.64 or 1.68, but is not limited thereto. It is preferably 1.5 to 1.6.
[0049] Preferably, reference Figure 5 In some embodiments of the utility model, the solar cell front anti-reflection film comprises a titanium dioxide film 2, a tin dioxide film 3, a silicon nitride film 4 and a silicon oxide film 5 sequentially stacked on a silicon substrate 1, wherein the silicon nitride film 4 comprises a first silicon nitride film 41, a second silicon nitride film 42 and a third silicon nitride film 43 sequentially arranged on the tin dioxide film 3. In the solar cell front anti-reflection film, the refractive index of each film layer decreases sequentially from close to the silicon substrate 1 to far away from the silicon substrate.
[0050] The silicon substrate 1 may be an N-type single crystal silicon wafer, a P-type single crystal silicon wafer, an N-type polycrystalline silicon wafer or a P-type polycrystalline silicon wafer, but is not limited thereto. Before preparing the anti-reflection film, the silicon substrate 1 is pre-treated, which may include texturing, diffusion, etching, back passivation and other processes, but is not limited thereto.
[0051] The present invention is further described below with specific embodiments:
[0052] In Examples 1 to 3 and Comparative Examples 1 to 3, the front anti-reflection film of the solar cell includes a titanium dioxide film (refractive index 2.25), a tin dioxide film (refractive index 1.92), a first silicon nitride film (refractive index 1.75), a second silicon nitride film (refractive index 1.66), a third silicon nitride film (refractive index 1.51) and a silicon oxide film (refractive index 1.36) stacked on a silicon substrate in sequence, and the specific thicknesses thereof are shown in Table 1:
[0053] Table 1 Thickness of each layer in Examples 1 to 3 and Comparative Examples 1 to 3
[0054]
[0055] In Comparative Example 4, the anti-reflection film on the front side of the solar cell includes a tin dioxide film (10 nm), a titanium dioxide film (10 nm), a first silicon nitride film (15 nm), a second silicon nitride film (35 nm), a third silicon nitride film (20 nm) and a silicon oxide film (15 nm) stacked on a silicon substrate in sequence, and the refractive index of each layer is the same as that of Examples 1 to 3.
[0056] The solar cell anti-reflection films of Examples 1 to 3 and Comparative Examples 1 to 4 were prepared into bifacial PERC cells and tested. The results are shown in Table 2 below:
[0057] Table 2 Test results of various embodiments and comparative examples
[0058] Conversion efficiency Example 1 23.72% Example 2 23.71% Example 3 23.77% Comparative Example 1 23.65% Comparative Example 2 23.67% Comparative Example 3 23.53% Comparative Example 4 23.70%
[0059] It can be seen from the above table that the front anti-reflection film of the utility model can effectively improve the photoelectric conversion efficiency of the solar cell. By comparing Example 3 with Examples 1-2, it can be seen that the photoelectric conversion efficiency can be further improved by optimizing the thickness of the titanium dioxide film and the tin dioxide film.
[0060] In addition, in the case where the titanium dioxide film and the tin dioxide film are respectively lacking in Comparative Example 1 and Comparative Example 2, the conversion efficiency of the solar cell is reduced compared to the case where the two film layers are present in combination, and the comparison of the final test data of Example 3 and Comparative Examples 1 to 3 shows that the titanium dioxide film and the tin dioxide film not only play a role in improving the conversion efficiency, but also the combination of the two produces a synergistic effect, achieving unexpected technical effects. At the same time, through the comparative test of Example 3 and Comparative Example 4, it can be seen that the arrangement order of the titanium dioxide film and the tin dioxide film also has an important influence on the conversion efficiency of the final solar cell.
[0061] The above disclosure is only a preferred embodiment of the present invention, and certainly cannot be used to limit the scope of rights of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope covered by the present invention.
Claims
1. A solar cell front anti-reflection film, arranged on a silicon substrate, characterized in that: It includes a titanium dioxide film and a tin dioxide film stacked in sequence; The refractive index of the tin dioxide film is smaller than that of the titanium dioxide film, and the thickness of the tin dioxide film is the same as or different from that of the titanium dioxide film.
2. The solar cell front anti-reflection film according to claim 1, characterized in that: The titanium dioxide film has a thickness of 5 nm to 15 nm and a refractive index of 2.1 to 2.3; The tin dioxide film has a thickness of 5nm to 15nm and a refractive index of 1.9 to 2.
0.
3. The solar cell front anti-reflection film according to claim 1, characterized in that: Also includes a silicon nitride film disposed on the tin dioxide film; The refractive index of the silicon nitride film is smaller than the refractive index of the tin dioxide film.
4. The solar cell front anti-reflection film according to claim 3, characterized in that: The silicon nitride film has a thickness of 10 nm to 150 nm and a refractive index of 1.5 to 1.
8.
5. The solar cell front anti-reflection film according to claim 1, characterized in that: The invention also includes a silicon oxide film disposed on the tin oxide film, wherein the refractive index of the silicon oxide film is smaller than the refractive index of the tin oxide film.
6. The solar cell front anti-reflection film according to claim 3, characterized in that: The invention also includes a silicon oxide film disposed on the silicon nitride film, wherein the refractive index of the silicon oxide film is lower than the refractive index of the silicon nitride film.
7. The solar cell front anti-reflection film according to claim 5 or 6, characterized in that: The silicon oxide film has a thickness of 5 nm to 20 nm and a refractive index of 1.1 to 1.
4.
8. The solar cell front anti-reflection film according to claim 3 or 6, characterized in that: The silicon nitride film includes a first silicon nitride film, a second silicon nitride film and a third silicon nitride film stacked in sequence; The refractive index of the third silicon nitride film is lower than that of the second silicon nitride film, and the refractive index of the second silicon nitride film is lower than that of the first silicon nitride film.
9. The solar cell front anti-reflection film according to claim 8, characterized in that: The first silicon nitride film has a thickness of 10 nm to 20 nm and a refractive index of 1.5 to 1.8; The second silicon nitride film has a thickness of 20 nm to 50 nm and a refractive index of 1.5 to 1.7; The third silicon nitride film has a thickness of 10 nm to 40 nm and a refractive index of 1.5 to 1.
7.
10. A solar cell, characterized in that: The invention comprises the solar cell front anti-reflection film as claimed in any one of claims 1 to 9.
